Price Volatility and Financial Instability - Leon, Gene (IMF Working Papers; Working Paper, 2001)
Statistical measures of the volatility of exchange rates, interest rates, and stock prices are estimated for a number of countries. Periods of high volatility are identified and compared with periods of financial difficulty. The results indicate that GARCH models of volatility could be potentially useful in assessing financial soundness. Daily data are more revealing, but monthly series allow comparisons among many countries. Country specific models may be needed for more reliable inference.